2008
DOI: 10.1186/1476-069x-7-29
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac autonomic activity and blood pressure among Nunavik Inuit adults exposed to environmental mercury: a cross-sectional study

Abstract: Background: Mercury is a contaminant that reaches high levels in Nunavik (North of Quebec). It is transformed into methylmercury (MeHg) and accumulated in marine mammals and predator fish, an important part of the traditional Inuit diet. MeHg has been suggested to affect BP in adults and children while the influence on HRV has only been studied in children. We aimed to assess the impact of MeHg levels on HRV and BP in Inuit adults from Nunavik.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 41 publications
2
67
1
Order By: Relevance
“…Regarding studies conducted in adults, we have previously reported a positive association between mercury and SBP and PP in a smaller group of only 205 Inuit adults Ն40 years of age with valid Holter data. 22 However, in the current study including more adults Ն40 years of age, as well as younger adults, we obtained consistent results. Our results are also in accordance with those published by Fillion et al 12 They observed that individuals with higher hair mercury levels had higher risk of increased SBP.…”
Section: Discussionsupporting
confidence: 74%
“…Regarding studies conducted in adults, we have previously reported a positive association between mercury and SBP and PP in a smaller group of only 205 Inuit adults Ն40 years of age with valid Holter data. 22 However, in the current study including more adults Ն40 years of age, as well as younger adults, we obtained consistent results. Our results are also in accordance with those published by Fillion et al 12 They observed that individuals with higher hair mercury levels had higher risk of increased SBP.…”
Section: Discussionsupporting
confidence: 74%
“…Also, in addition to the HRV traditional risk factors (age, sex, obesity, insulin sensitivity [measured as HOMA-IR], cholesterol [HDL and LDL-cholesterol] and triglycerides levels, smoking habits, alcohol consumption, physical activity, menopausal status and socioeconomic status), we considered the impact of mercury exposure. These results are particularly important since mercury has been associated with decreased HRV in populations with a high mercury intake, including the Inuit from Nunavik (22)(23)(24). However, no impact of mercury on resting HR was observed in this population (unpublished observations) and in other studies (22,24), which suggests that fish consumption may offer some protection regarding resting HR even in highly mercury-exposed populations.…”
Section: Discussionmentioning
confidence: 49%
“…Fish and marine mammals accumulate high quantities of mercury that has been associated with decreased HRV in adults (22)(23)(24). Since it is important for Inuit to know the risks and benefits of the traditional diet, we aimed to assess the impact of n-3 PUFAs on HRV and resting HR taking into account potential confounding factors.…”
Section: Introductionmentioning
confidence: 99%
“…Grandjean et al (2004) did not observe an influence of methyl mercury exposure on blood pressure and heart rate in children, but they described an influence of methyl mercury on the cardiac autonomic activity. The other studies summarised in the table as well as those not cited in the table like Valera et al (2008; and Fillion et al (2006) also do not provide a consistent result on the influence of methyl mercury exposure on blood pressure. Some of these studies investigated only small numbers of patients, others did not adequately control for the influence of fish intake e.g.…”
Section: Study Locationmentioning
confidence: 81%